2015
DOI: 10.2190/ns.24.4.g
|View full text |Cite
|
Sign up to set email alerts
|

A Growing Fire Hazard Concern in Communities: Home Oxygen Therapy and Continued Smoking Habits

Abstract: The Safe Home Care Project investigated both qualitatively and quantitatively a range of occupational safety and health hazards, as well as injury and illness prevention practices, among home care aides in Massachusetts. This article reports on a hazard identified by aides during the study's initial focus groups: smoking by home care clients on long-term oxygen therapy. Following the qualitative phase we conducted a cross-sectional survey among 1,249 aides and found that medical oxygen was present in 9 percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 13 publications
2
20
1
Order By: Relevance
“…Six of 12 focus groups that were conducted during the Safe Home Care Project's presurvey qualitative phase brought up the problem of patients smoking while receiving home oxygen therapy. Below are examples from 3 different focus group reports by home care aides that illustrate this scenario34:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six of 12 focus groups that were conducted during the Safe Home Care Project's presurvey qualitative phase brought up the problem of patients smoking while receiving home oxygen therapy. Below are examples from 3 different focus group reports by home care aides that illustrate this scenario34:…”
Section: Resultsmentioning
confidence: 99%
“…Medical oxygen combined with smoking or other sources of ignition is a serious fire and explosion hazard that threatens not only workers who visit homes but also community members (scenario 10) 34. Home cooking equipment, smoking materials, and heating equipment are leading causes of residential structure fires, injuries, and civilian home fire deaths 37.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are not the first to recognize the risk posed by smoking on oxygen therapy to health care workers. A recent review identified that 9% of home health aid visits were to residences with home oxygen of which 25% patients were identified as smokers [12]. …”
Section: Discussionmentioning
confidence: 99%